Criminal legal means to protect refugee women from crimes of slavery and sexual persecution and ways to confront them - Mohammed Rashid Hassan (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
this study will elaborate and treat with two new international crimes which have been enacted in contemporary international criminal law system and these crimes are: sexual slavery and persecution on gender bases especially against the women refugees. its worthy to note that the committing these rimes took widespread form with increasing number of international and internal conflicts all over the world. for example the international community witnessed brutal and inhumane attacks against the women in last year's specifically what happened in Sinjar against the Yazidis women ,the same acts also have been committed in Nigeria by Boko Haram group against the girls and women .consequently the mentioned acts can be consider as crimes against dignity also its affect the peace and security all over the world .by this research we aimed to examine the legal requirements of these crimes according to ICC statues also according to recent judicial decisions ordered by international criminal tribunals dealing with the subjected crimes. lastly we determined the judicial mechanisms available to prosecute the offenders and then we determined the suitable ways to make a complement judicial record for thiese systematic acts.